Importance of Project-oriented Organizational Culture in Knowledge Management Processes - Alghail, Adnan Ali; Liu, Yao; Cheng, Jack Kie (Global Journal For Research Analysis(GJRA), 2017)
As organizations are seeking for an acceptable knowledge management environment, they use knowledge to the greatest advantage in their ongoing work projects. In other words, Knowledge Management (KM) is vital to successfully undertake projects. Therefore, It is necessary to ensure that they are using sufficient knowledge management processes for this purpose in a supportive project-oriented organizational culture (POOC). Nowadays, the fullment and usage of KM processes are essential for modern organizations to evolve their culture habits and managerial routines, to build a competitive culture environment and to achieve a high standard project organizational culture. This paper aims to highlight the importance of project-oriented organizational culture toward using the knowledge management processes for gaining a successful project deliverables and achieving the organization goals. It provides the fundamental description of each process of the knowledge management. It explains each processes in regards to the project-oriented organizational culture, even identifying why the project organizational culture is considered an important principle for the KM processes success. Hopefully, the outcomes of this paper shall provide enriching endings to leaders and managers in the organization intaking consideration into their Project-oriented Organizational Culture for enhancing the knowledge management processes.